SPE Improved Oil Recovery Conference 2020
DOI: 10.2118/200441-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Chemical Structure and its Impact on EOR Performance

Abstract: Polymer flooding is a mature EOR technology that has seen an increasing interest over the past decade. Co-polymers of Acrylamide (AMD) and Acrylic Acid (AA) have been the most prominent chemicals to be applied, whereas sulfonated polymers containing 2-Acrylamido-tertiary-butyl sulfonic acid (ATBS) have been used for higher temperature and/or salinity conditions. The objective of this study was to generate guidelines to aid in the selection of appropriate polyacrylamide chemistry for each field case. Our main f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The polymers can be easily synthesised and hydrolysed with different copolymers to improve the adsorption performance [ 14 ]. Some examples include hydrolysed polyacrylamide (HPAM) and sulfonated polyacrylamide (SPAM), which SPAM has a bulkier copolymer of deprotonated 2-acrylamide-tertiary-butyl sulfonic acid and exhibit higher thermal stability as a polymer flooding agent [ 13 , 15 ]. There is a well-established guideline for the evaluation and selection of these water-soluble polymers in different operating conditions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polymers can be easily synthesised and hydrolysed with different copolymers to improve the adsorption performance [ 14 ]. Some examples include hydrolysed polyacrylamide (HPAM) and sulfonated polyacrylamide (SPAM), which SPAM has a bulkier copolymer of deprotonated 2-acrylamide-tertiary-butyl sulfonic acid and exhibit higher thermal stability as a polymer flooding agent [ 13 , 15 ]. There is a well-established guideline for the evaluation and selection of these water-soluble polymers in different operating conditions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the stability of polymers is inferior under severe conditions. It has been observed that copolymers can significantly enhance the temperature and salt tolerance of monomer polymers. Extensive investigations have been performed to explore the fundamental mechanisms of polymer-enhanced foam (PEF) flooding, and the results demonstrated that polymers could extend the longevity of the foam mainly in two ways. , One of the noticeable advantages of applying polymer was to viscosify the foam lamella, as it was reported that the drainage time of the foam lamellae was directly proportional to its viscosity . Second, the thickness of foam lamella stabilized by polymers could be dramatically increased, which inhibited the bubble coarsening and collapse .…”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advances have triggered the development of novel acrylamide-based polymers that contain unique monomers, such as N-vinylpyrrolidone and sodium ATBS, which provide stability at high-temperature and -salinity conditions (Jabbar et al 2018;Beteta et al 2020). However, the field applications of these polymers are limited due to their high production costs.…”
Section: Introductionmentioning
confidence: 99%